EMPOWERMENT OF HIGH SCHOOL STUDENTS IN ESTABLISHING A SAFE COMMUNITY: PROMOTIVE EFFORTS TO CONTROL AND MANAGEMENT OF TRAFFIC ACCIDENTS IN LAMONGAN - Erna Dwi Wahyuni; Arina Qona'ah; Sriyono Sriyono (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Introduction: Traffic accidents can have an impact both physically, psychologically, and socially. People still have low awareness and knowledge both in driving and in providing first aid to victims of traffic accidents. Students can become one of the human resources that can be used to provide education to the community or their group regarding the control and handling of past accidents.Methods: The method used is through education and training which includes safety riding and first aid. Extension activities were carried out online by using the zoom while training activities were carried out offline at SMA N 2 Lamongan. The training materials provided to students include basic life support, and splints, and ambulation. The training is carried out using lectures, demonstrations - simulations, and discussions. Media for delivering technology is also prepared, namely in the form of materials and props.Results: The students' knowledge of first aid before the activity was less than 23 people (69.69%), enough for 8 people (24.24%), and good for 2 people (6.06%). While the knowledge after the activity is less than 1 person (3.03%), only 16 people (48.48%) and good 16 people (48.48%). The results of the pre-test and post-test showed an increase in students' knowledge about first aid.Conclusion: Efforts to establish a safe community can be done by involving students as one of the components of society which is expected to become agents of change in controlling and handling traffic accidents.Keywords: safety riding, safe community, promotive, accident first aid